2020
DOI: 10.1186/s12957-020-01834-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lymph node metastasis in early gastric cancer: a single institutional experience from China

Abstract: Background: Lymph node metastasis (LNM) has a strong influence on the prognosis of patients with early gastric cancer (EGC). The aim of this study was to reveal the incidence of LNM and evaluate risk factors for LNM to determine the appropriate treatment for EGC in a Chinese population. Methods: Patients who underwent radical gastrectomy with lymph node dissection for EGC between 2012 and 2017 were retrospectively analyzed. Univariate and multivariate analyses were conducted to identify clinicopathological fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 30 publications
4
29
1
Order By: Relevance
“…The incidence of male GC is known to be higher than that of female GC, but the mortality rate of female patients with GC is higher than that of male patients ( 15 17 ). In this study, female patients with EGC had a higher LNM ratio than male patients (17.0% vs. 10.4%), which was consistent with previous studies ( 8 , 10 , 25 ). It is therefore necessary to analyze the risk factors for LNM in male and female patients with EGC separately.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The incidence of male GC is known to be higher than that of female GC, but the mortality rate of female patients with GC is higher than that of male patients ( 15 17 ). In this study, female patients with EGC had a higher LNM ratio than male patients (17.0% vs. 10.4%), which was consistent with previous studies ( 8 , 10 , 25 ). It is therefore necessary to analyze the risk factors for LNM in male and female patients with EGC separately.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have explored the risk factors for LNM of EGC patients and established corresponding prediction models (8)(9)(10)(11). Previous study reported that the female sex is an independent risk factor for LNM in patients with EGC (12).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, the incidence of LNM in patients with EGC regardless of T1a or T1b was 15-24% [28,29]. Recently, Chen et al reported that the LNM rate was 16.7% in EGC (8.7% in T1a, 24.6% in T1b) in their retrospective study that enrolled 1,033 patients with EGC [30]. In agreement with results of previously reported studies, our data showed that the incidence rates of LNM were 12.38% in T1a stage, 27.94% in T1b stage, and 18.36% in whole EGC.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to exclusion of nodal disease prior to ER for EGC, the use of EUS has again been associated with variable accuracy. In a 2008 meta-analysis, the pooled sensitivity of EUS for N1 disease was as low as 58.2%[ 82 ]. More recent data have shown an improved sensitivity and specificity of 74%-83% and 67%-70% in detecting nodal positivity[ 75 , 83 , 84 ].…”
Section: Endoscopic Diagnosis Of Gastric Neoplasiamentioning
confidence: 99%